Evolutionary Analyses and Natural Selection of Betaine-Homocysteine S-Methyltransferase (BHMT) and BHMT2 Genes - Ganu, Radhika S. (PLoS One, 2015)
Betaine-homocysteine S-methyltransferase (BHMT) and BHMT2 convert homocysteine to methionine using betaine and S-methylmethionine, respectively, as methyl donor substrates. Increased levels of homocysteine in blood are associated with cardiovascular disease. Given their role in human health and nutrition, we identified BHMT and BHMT2 genes and proteins from 38 species of deuterostomes including human and non-human primates. We aligned the genes to look for signatures of selection, to infer evolutionary rates and events across lineages, and to identify the evolutionary timing of a gene duplication event that gave rise to two genes, BHMT and BHMT2. We found that BHMT was present in the genomes of the sea urchin, amphibians, reptiles, birds and mammals; BHMT2 was present only across mammals. BHMT and BHMT2 were present in tandem in the genomes of all monotreme, marsupial and placental species examined. Evolutionary rates were accelerated for BHMT2 relative to BHMT. Selective pressure varied across lineages, with the highest dN/dS ratios for BHMT and BHMT2 occurring immediately following the gene duplication event, as determined using GA Branch analysis. Nine codons were found to display signatures suggestive of positive selection; these contribute to the enzymatic or oligomerization domains, suggesting involvement in enzyme function. Gene duplication likely occurred after the divergence of mammals from other vertebrates but prior to the divergence of extant mammalian subclasses, followed by two deletions in BHMT2 that affect oligomerization and methyl donor specificity. The faster evolutionary rate of BHMT2 overall suggests that selective constraints were reduced relative to BHMT. The dN/dS ratios in both BHMT and BHMT2 was highest following the gene duplication, suggesting that purifying selection played a lesser role as the two paralogs diverged in function.